اللجوء السياسي بين الشريعة الإسلامية والقانون الدولي: دراسة مقارنة تقويمية: Political asylum between Islamic law and international law: An evaluative comparative study - Jaghama, Maher A.A.; Arif Ali Arif (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث باندلاع ثورات "الربيع العربي" تحديداً، زادت حالات اللجوء بين المسلمين. اُستقبل بعض هؤلاء المسلمين من قبل عددٍ من الدول الأوروبية غير المُسلمة، وعددٍ قليلٍ من الدول الإسلامية. في ظل هذه الأجواء، تزيد حالات البحث والفضول حول أحكام تعامل الشريعة الإسلامية من جهة والقانون الدولي من جهةٍ أخرى مع مسألة اللجوء سواء السياسي أو الإنساني، وبالتالي يقع على عاتق الباحثين مسؤولية سبر أغوار هذه الأحكام وتقديمها على نحوٍ علمي مفصل للقارئ. يهدف هذا البحث إلى الإبانة عن موضوع اللجوء السياسي بين الشريعة الإسلامية والقانون الدولي من خلال تقييم قوانين الحكومية الحكومة التركية حيال العدد الهائل من اللاجئين السياسيين إليها من الدول العربية. ومن أهم نتائج البحث هو أن النظام الدولي المعاصر قائم على أساس الدولة الوطنية أو القومية، ومن ثم لا تستطيع الدول الإسلامية تطبيق أحكام الجوار من دون اعتبارات اقتصادية أو سياسية. ABSTRACT With the outbreak of the “Arab Spring” revolutions in particular, refugee cases among Muslims increased. Some of these Muslims were received by a number of non-Muslim European countries, and a small number of Islamic countries. In light of this atmosphere, cases of research and curiosity about the provisions of Islamic law on the one hand and international law on the other hand with the issue of asylum, whether political or humanitarian, are increasing. Therefore, it is the responsibility of researchers to explore the depths of these provisions and present them in a detailed scientific manner to the reader. This research aims to clarify the issue of political asylum between Islamic law and international law by evaluating the Turkish government’s laws regarding the huge number of political refugees coming to it from Arab countries. One of the most important results of the research is that the contemporary international system is based on the national or national state, and therefore Islamic countries cannot implement the provisions of neighborhood without economic or political considerations.